Growth and survival of post larvae of tiger shrimp (Penaeus monodon Fabr.) through the administration of probiotics with different doses - Ali Usman; Rochmady Rochmady (Sekolah Tinggi Ilmu Pertanian Wuna, 2017)
One of the factors that affect the growth of tiger shrimp is the quality of feed. Nutrient content in feed such as protein, carbohydrate and fat, generally used as a parameter of feed quality. Feed consumed by shrimp is not all digested, one of which depends on the enzymatic ability of the shrimp digestive tract. The use of probiotic bacteria in addition to having the ability to reduce colonies, inhibit the growth of pathogenic bacteria, and neutralize water quality, probiotic bacteria can help digestibility of the intestine. The aim of this research is to know the growth and survival of post larvae of shrimp (Penaeus monodon Fabr.) Through the provision of probiotics with different doses. The research was conducted at Balai Fish Fishing Hall of Muna Regency, Southeast Sulawesi, Indonesia. Post larva shrimp tiger (PL-20) of 120 tails, maintained for 28 days. The tested treatment was probiotic dose 5 ml (treatment A), dose 10 ml treatment B), dose 15 ml (treatment C), and without probiotics (control). Probiotics are given every 7 days on water maintenance media using a pipette (0.5-20 ml scale). Weighing results showed relatively high post-larva shrimp larvae growth of 400.00% (treatment B); 291.67% (treatment C); of 233.33% (treatment A) and equal to 58.33% (Control). Variation analysis result showed that giving of probiotic with different dose gave real effect (P<0,01) to relative growth of postlarva prawn weights (P. monodon Fabr.). Provision of probiotics has no significant effect on postlarva tiger prawn survival rate (P. monodon Fabr.). The survival rate of post larvae of tiger shrimp during the study was in the range 66.67-83.33%.